Smartphone for Next Generation Attendance System and Human Resources Payroll System - Benfano Soewito; Fergyanto E. Gunawan; Manik Hapsara (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
A wide variety  of current attendance system can be found easily in the market, but there are still some deficiencies in the attendance system;  how the company  will control  employees are  outside  the office building  and  how employees can take  ad- vantage of the attendance system to view a variety of information needed.  The  modern  attendance system must  integrated with a human  resources management and payroll  system. Others  issues with  current  attendance system,  beside  could  not  control  the staff  who  work  outside  the  office are  conventional  attendance system that  spends  a lot of paper  and  a long process  due to be entered  manually  into  the  system  for  processing  payroll,  while the  electronic  attendance system  with  limited  device can  cause queues  at  the  time  employee entry  and  exit the  office building. In  this  work,  we introduce online  attendance system on mobile devices and  is integrated with the payroll  system. It is a system created  to overcome some of the limitations  that occur in manual or electronic attendance system which is often conventionally used today. We utilized Global Positioning System (GPS), microphone, and fingerprint scanner  that available on a smartphone or others mobile  devices. We developed  our application base  on  android platform   because  the  android is the  most  platforms   that  have been using in the most mobile devices. Using our proposed methodology, the employee can do attendance using their  mobile devices and the do not need to be in queue and the employee who work outside the office also can do the attendance. Our  research showed that our proposed methodology can used for the next generation  absence  system.